The Effect of Interest Rate Risk on Financial Performance with the Mediating Variable of Banking Security Level (Study on Commercial Banks that Go Public in BEI) - Retno Belinda; Zulfa Irawati (Journal La Sociale, 2024)
Rapid internal and external development has been witnessed by the banking industry, particularly at the domestic level, where the usage of innovative financial instruments has grown dramatically. Banks mediate transactions between different economic activity, receive deposits, create money, and offer thorough banking services to individuals, organizations, and other banks. They also provide credit facilities. As a measure of a nation's spending and investing habits, the interest rate plays a significant role in conserving money and choosing how to spend it. Banking institutions are beginning to understand the significance of risk management in preparing for potential threats to their businesses. Banking executives in Indonesia must mitigate these risks by enhancing their institutions' bottom lines. The purpose of this research was to examine the relationship between interest rate risk and financial performance in Indonesian banking organizations, with the level of banking security serving as a moderation variable. This quantitative analysis employs a sample of 24 commercial banks that have listed on the IDX between 2019 and 2022 as its research population. The findings shown that Interest Rate Risk significantly impacts Banking Security Level, Financial Performance, and Financial Performance via Interest Rate Risk via Banking Security Level.